Online teaching for ethnic minority students in Vietnam during the COVID-19 pandemic - A qualitative study (Revista de Investigaciones Universidad del Quindío, 2022)
The COVID-19 pandemic has had a comprehensive and profound impact on Vietnamese education. In response to the pandemic, many localities have organized continuous online teaching for a long time. Teaching activities must change from planning, teaching organization, and assessment to adapting to the online teaching environment. The study aims to assess the current status of online teaching of ethnic minority students in Vietnam in aspects from teaching conditions and implementation practices to evaluate the effectiveness of online teaching.
Keywords: Online education; Covid 19; students; ethnic minorities; Vietnam